The Effect of Hypnosis on the Academic Performance of Students with Learning Disabilities in School Examinations: A Single-Group Pretest-Posttest Experimental Study - Chia, Noel Kok Hwee (Journal of the American Academy of Special Education Professionals, 2013)
This paper explores the use of hypnosis, which is one specific specialized practice of complementary and alternative medicine or treatment (CAM/T), and its effectiveness as a treatment for children with learning disabilities. The World Health Organization (2002) has reported an increase in number of people turning to CAM/T for help when they feel that conventional medicine and treatment fail to solve their chronic issues related to mental and/or physical health. In Singapore, reports in mass media point to an increasing number of parents seeking CAM/T to help their children with special needs, especially those with attention deficit/hyperactivity disorder, autism spectrum disorder and learning disabilities, cope with their daily living activities and studies. The survey study reported in this paper was done in 2007-2008 involving 102 participants. Out of this number, only a small sample of 11 participating parents had sent their children with learning disabilities for hypnosis or hypnotherapy, with the hope that the treatment would help their children to perform better academically.